The role of passion, need satisfaction, and conflict in athletes` perceptions of burnout - Lopes, M.; Vallerand, R. J. (Psychology of Sport and Exercise, 2020)
This research examined the role of harmonious and obsessive passion in athletes` perceptions of burnout. Two studies using correlational designs were carried out with different samples of athletes of varied skill levels. In Study 1, we found that obsessive passion was positively, and harmonious passion negatively, associated with burnout perceptions in athletes. Results of Study 2 replicated the findings of Study 1 and in addition used Structural Equation Modeling analyses to support the mediating role of conflict and need satisfaction in the relation between types of passion for sport and athletes` perceptions of burnout. Furthermore, it was found that harmonious passion for a second activity was associated with lower athletes` perceptions of burnout; while obsessive passion for a second activity was directly associated with it. The results have important implications for theory and research on passion as well as burnout in sport.